Foreign Vocabulary In Sign Languages: A Cross-Linguistic Investigation Of Word Formation - Brentari, Diane (New Jersey : Lawrence Erlbaum Associates, 2001)
The contributions contained in this volume also examine the social attitudes and cultural in this values that play a role in this linguistic process.
Borrowed Elements in Sign Language: A Window on Word Formation Diane Brentari
Keywords: Sign Languages